Creating team ambidexterity: The effects of leader dialectical thinking and collective team identification. Issue 2 (April 2022) - Han, Guohong; Bai, Yuntao; Peng, Gang
Abstract: In the current, increasingly dynamic environment, more attention is being devoted to ambidexterity (both explorative and exploitative learning), as it is beneficial to organizational functioning. Despite an abundance of research on organizational ambidexterity, there is a paucity of research examining team-level ambidexterity. In a cross-level empirical study, we examine a leader's dialectical thinking as an antecedent of team-level ambidexterity. We also incorporate collective team identification as a moderator in the study. Our findings support that a leader's dialectical thinking can help facilitate team ambidexterity that, in turn, improves employee performance. Those teams whose members have strong team identification and whose leader is high in dialectical thinking will reap the most benefit from team ambidexterity.